2014
DOI: 10.1007/s10384-014-0352-2
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic criteria for IgG4-related ophthalmic disease

Abstract: Immunoglobulin G4 (IgG4)-related disease is a novel clinical entity characterized by infiltration of IgG4-immunopositive plasmacytes and elevated serum IgG4 concentration accompanied by enlargement of and masses in various organs, including the lacrimal gland, salivary gland, and pancreas. Recent studies have clarified that conditions previously diagnosed as Mikulicz disease as well as various types of lymphoplasmacytic infiltrative disorders of the ocular adnexa are consistent with a diagnosis of IgG4-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(116 citation statements)
references
References 28 publications
4
109
1
2
Order By: Relevance
“…Similar cases had been reported subsequently by many facilities [4]. It is now known that IgG4-related ophthalmic lesions are not limited to the lacrimal glands but may manifest with various patterns in the orbit and ocular tissues such as extraocular muscles, orbital nerve, and eyelid [6].…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Similar cases had been reported subsequently by many facilities [4]. It is now known that IgG4-related ophthalmic lesions are not limited to the lacrimal glands but may manifest with various patterns in the orbit and ocular tissues such as extraocular muscles, orbital nerve, and eyelid [6].…”
Section: Discussionsupporting
confidence: 48%
“…Recent studies have confirmed that conditions previously diagnosed as Mikulicz disease as well as various types of lymphoplasmacytic infiltrative disorders are consistent with a diagnosis of IgG4-related disease [1,2]. After the establishment of comprehensive diagnostic criteria for IgG4-related disease in 2012 [3], the diagnostic criteria for IgG4-related ophthalmic disease (IgG4-ROD) have recently been reported, based on both clinical and histopathologic features of ocular lesions [4]. We report a unique case of IgG4-ROD involving the sclera, which had been misdiagnosed as intraocular tumor for over 10 years.…”
Section: Introductionmentioning
confidence: 87%
“…According to the diagnostic criteria for IgG4-ROD,9 19 (68%) patients had ‘probable’ and 9 (32%) had ‘definitive’ diagnoses (figure 1). The clinical characteristics of patients are summarised in tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Only patients with biopsy-proven IgG4-ROD, who were followed up for >6 months after the initial treatment, were included in this study. Diagnosis of IgG4-ROD was based on the criteria by the Japanese Study Group for IgG4-ROD in 2014, and the patients were categorised as ‘probable’, ‘possible’ or ‘definitive’ according to the criteria9 (box 1). All patients underwent a baseline systemic evaluation; review of medical history, physical examination, laboratory tests (including serum IgG, IgG subclass, rheumatoid factor and IgE level) and imaging studies (neck, chest, abdominal and pelvic CT scans, and/or positron emission tomography).
Diagnostic criteria for IgG4-related ophthalmic disease, 20149

(1) Imaging studies show enlargement of the lacrimal gland, trigeminal nerve or extraocular muscle as well as masses, enlargement or hypertrophic lesions in various ophthalmic tissues.

(2) Histopathological examination shows marked lymphocyte and plasmacyte infiltration, and sometimes fibrosis.

…”
Section: Methodsmentioning
confidence: 99%
“…The overall schema, however, is relatively consistent. Diagnosis relies upon a combination of clinical examination, imaging, blood testing and histopathology [17,21]. Examination and imaging should demonstrate enlargement or a mass in at least one organ [17].…”
Section: Diagnostic Featuresmentioning
confidence: 99%